Variations in hyphen usage when writing 'Taglish' verbs - Dench, Alison (2004)
When English root words are mapped onto Tagalog stems 'Taglish' verbs are created. These verbs are inflected for both focus and aspect in the same way that Tagalog verbs are; however, despite the fact that the Tagalog orthographic system has strict rules on hyphen usage, writers of Taglish verbs are showing variation in how they use such hyphens. In analyzing sentences from just five samples, six differences were discovered. Such results suggest that Taglish is an orthographic system still in flux.
Includes bibliographical references (pages 48-49).